DESULFURISASI DAN DEASHING PADA BATUBARA MENGGUNAKAN NaOH DAN HCl SEBAGAI LEACHING AGENT (Jurnal Geomine, 2019)
Desulfurization and deashing research on coal, in addition to improving the quality of coal is also an attempt to reduce the elements that cause the occurrence of environmental pollution. Coal samples in this study originated from Tondongkura Village, Tondong Tallasa District, Pangkep Regency, South Sulawesi Province. Desulfurization and deashing of coal from Tondongkura have been carried out using chemical solution NaOH and HCl as leaching agents.  In order to determine the effect of several factors in the process, the experiment conducted in several variables, namely time, temperature, particle size, concentration of NaOH and HCl. The results of the study showed the total sulfur content from 3.67% decreased to 2.93%, the maximum percentage of total sulfur reduction was 20.03%. Whereas the maximum percentage reduction of ash content was 12.29%, from the initial ash content of 27.44% decrease to 24.06%. HCl was used as leaching agent for second stage leaching on previously leached coal using NaOH under optimum conditions. From the experiments it was a maximum percentage reduction of total sulfur of 3.67% was decreased to 2.11% or the maximum percentage of total sulfur reduction was 42,51% and the ash content of the initial sample was 27.44% decreased to 22.04% or the maximum percentage of ash reduction was 19.67%.